Pengaruh Massa Dan Ukuran Partikel Adsorben Daun Nanas Terhadap Efisiensi Penyisihan Fe Pada Air Gambut - reyra, Anilza Silvi; Daud, Syarfi; Yenti, Silvia Reni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Peat water is surface water are blackish brown and metals Fe which requires effective and efficient processing to be worthy for use by the public. Various types of adsorbents continue to be developed, one of which is the pineapple leaf adsorbent. The purpose of this study was to determine metal removal efficiency of Fe in the peat water, calculating the adsorption capacity and determine the appropriate type of isotherm. Fixed variables used in this study is the stirring speed of 120 rpm and a contact time of 90 minutes. For independent variables used consisted of adsorbent mass variation of 1,5; 2; 2,5; 3 g and a particle size variation 80, 100 and 120 mesh. Removal efficiency of Fe metal concentrations higher 76,14% by mass of adsorbent 3 g with a particle size of 120 mesh. Metal adsorption capacity of Fe achieved the highest on the mass of 1,5 grams with a particle size of 120 mesh amounted to 0,092 mg Fe / g . Types of adsorption isotherms corresponding to Fe by pineapple leaf adsorbents is Freundlich isotherm with R2 values of 0,927 for Fe.Keywords : Adsorption, Adsorbent, Peat Water, pineapple leaf